EFFECT OF SOLVENT EXTRACTED KARANJ CAKE WITH ENZYMES AND LIVER TONIC SUPPLEMENTATION ON PERFORMANCE, NUTRIENT DIGESTIBILITY AND ECONOMICS OF BROILER CHICKEN - M.V.L.N. RAJU and SRINIVAS GURRAM, DAIDA KRISHNA, V. RAVINDER REDDY, V. CHINNI PREETHAM (The Journal of Research, PJTSAU, 2022)
An experiment was conducted to evaluate the effect of dietary inclusion of solvent extracted karanj cake (SKC) and iso propyl alcohol (IPA) treated SKC supplemented with protease (4000 U/kg), phytase (400 U/kg) and liver tonic (0.1%) on performance, nutrient digestibility and returns over feed cost in broiler chickens. The inclusion of control and karanj cake wereincluded in diets on isocaloric and isonitrogenous basis at graded (6%) level making 12 treatments (T1 to T12). A total of 360 dayold commercial broiler chicks, which were distributed in a randomized block design into 12 groups with 6 replicates of 5 chicks each. The chicks were housed in battery brooders and fed experimental diets from 1 to 42 days of age. The results revealed that inclusion of IPA treated karanj cake and SKC at 6% level treated with enzymes and liver tonic supplementation significantly did notimprove the body weight gain, feed intake and feed conversion ratio compared to control groups. The percent retention of dry matter and crude protein were significantly (P